Research on broadcast and TV system interference of 700 MHz band in 5G network - Peijin LYU; Yun LU; Xiaokang YANG; Dan YANG; Yiyan YIN; Zhengyi GUO (Dianxin kexue)
There is a risk of co-channel interference from broadcast TV systems in the operation of 5G networks in the 700 MHz band, which seriously affects the network performance.Firstly, from the frequency configuration of broadcast TV system, the principle of interference by broadcast TV system in 5G network in 700 MHz band was discussed.Then, the interference characteristics of broadcast TV system were analyzed, and the interference identification algorithm of broadcast TV system based on frequency domain information was proposed for these characteristics.Finally, the accuracy of the algorithm identification was tested and verified to achieve the goal of interference optimization and avoidance through interference identification.